Effect of stress on arterial blood pressure In dental students - Tahani A Al–Sandook; Karama MT Al–Nuaimy; Maha T Al–Saffar (Al-Rafidain Dental Journal, 2007)
Aims: To study the effect of stress and fear on blood pressure that are imposed on student before attending examination in particular final year examination at the College of Dentistry. Subjects and Methods: Arterial blood pressure (indirect method ) was measured for 99 dental student (21 + 0.6 years) before 30 minutes of final examination on a particular subject and immediately after examination. Result: The data reflected a significant increase in systolic blood pressure before passing the final examination, whereas there was no significant increase in the diastolic blood pressure in all students. Conclusions: Stress produces a significant elevation in blood pressure that can be controlled by systemic defense mechanisms naturally present.